PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING - Yulia Prisselya Hutagalung; Sugih Sutrisno Putra (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to determine whether corporate social responsibility has a positive and significant effect on firm value, and whether profitability is able to strengthen the relationship of corporate social responsibility to firm value. This type of research uses quantitative methods. Data analysis techniques in this study use SPSS 25 tools. are classical assumption test, hypothesis test, regression analysis and MRA (moderated regression analysis). The result of the research is that CSR has no effect on firm value, and profitability is able to strengthen the relationship between CSR and firm value